UJI DAYA HAMBAT EKSTRAK DAUN KETEPENG CINA (Cassia alata L.) TERHADAP JAMUR PATOGEN Phytophthora palmivora PENYEBAB PENYAKIT BUSUK BUAH KAKAO (Theobromae cacao L.) - Suarni, Suarni; Panggeso, Johanes; Rosmini, Rosmini (AGROTEKBIS, 2017)
The study aimed is to find out the inhibitation level of leaves extract of Ketepeng China (Cassia alata L.) insome concentrations on the growth of Phytophthora palmivora funguson cocoa fruit. This study was arranged in Complete Randomized Design, with the extract concentrations tested were 0,5%, 1%, 1,5%, 2% and 2,5% on the growth of Phytophthora palmivora fungus diameter. This study was conducted on September to October 2015 in Pest and Disease Department Laboratory, Agriculture Faculty, Tadulako University. The result showed that the average extract concentration of 2,5% can better inhibitate the growth of Phytophthora palmivora fungus diameter (30.18%), and based on the analysis using simple linear regression, it showed that the concentration 2,5% has the higest dependent variable value with 30,48%.Â Key Words : Cocoa, extract leave, Ketepeng China (Cassia alata L.), Phytophthora palmivora.